Consep of Implementing Diagnostic Assessment in Learning Planning and Implementation - Winditiya Yuliana; Ach. Emil Salim (Edumaspul: Jurnal Pendidikan, 2023)
Assessment or assessment is an activity that has principles and strategies that can guide teachers and educational units in planning, implementing and evaluating learning. The intended learning includes the activity of formulating learning outcomes into learning objectives and how to achieve these learning objectives. While assessment is an activity during the learning process to find evidence of the achievement of learning objectives. In this guide, learning and assessment is a cycle; where the assessment provides information about the learning that needs to be designed, then the assessment is used to check the effectiveness of the ongoing learning. Therefore, the preferred assessment is a formative assessment that is oriented towards the development of student competencies. The government has determined Learning Outcomes which are the main reference in developing learning designs, especially for intra-curricular learning activities. This research facilitates the process of thinking about the effectiveness of diagnostic assessments in planning and implementing learning, which starts from analyzing learning outcomes, learning objectives develop a flow of learning objectives.